Conceptions About Curriculum, School Content and The teachers in the process to produce texts Curriculum in Argentina - Amantea, Alejandra; Cappeletti, Graciela Laura; Cols, Estela Beatriz; Feeney, Silvina (Education Policy Analysis Archives, 2004)
This work analyzes curriculum development processes that have taken place in Argentina during the period 1980-2000. The purpose of this article is to identify the main trends in the conceptions used by the key actors/designers of curriculum for school content, curricular texts and teachers´ place as interpreters of curricular texts. Three lines of thought are distinguished that have impacted curricular decision making processes carried out at the central levels of the system: the tradition of the General Didactics, the tradition of the Special Didactics, and the disciplinary tradition. Finally, this article concludes that a view of curriculum development as a social process needs to incorporate how cultural and political elements are articulated with technical decisions in the particular spaces and agencies where curricular texts are produced.